Mapping Geometric Minds: Exploring 3D Thinking Skills of Elementary School Students Using the Van Hiele Model - Nahdi, Dede Salim; Jatisunda, Mohamad Gilar; Cahyaningsih, Ujiati; Rasyid, Abdur; Hidayah, Ratna (Journal of Education For Sustainable Innovation, 2024)
This study investigates elementary school students' 3D geometric thinking skills using the Van Hiele model. The research employed a grounded theory approach, utilizing tests, observations, and interviews to assess students' geometric thinking levels across two elementary schools in West Java and Central Java, Indonesia. A total of 6 test items were developed based on Van Hiele's theory, targeting the visualization, analysis, and informal deduction levels. Results showed varied performance between the two schools. Students from the Majalengka school demonstrated stronger visualization skills (77.14%), while those from the Surakarta school showed better performance in analysis (67.86%) and informal deduction (53.57%). Overall, students exhibited a good foundational understanding of 3D shapes, with most achieving the visualization and analysis levels. However, challenges emerged at the informal deduction level, where students often opted for simpler problem-solving methods over more systematic approaches. The study highlights the effectiveness of the Van Hiele model in assessing geometric thinking development and provides valuable insights for curriculum development and teaching strategies. It emphasizes the need to reinforce visualization and analysis skills while gradually introducing more abstract and systematic thinking in geometry education. The findings contribute to the understanding of elementary students' 3D geometric thinking skills and offer a basis for improving geometry instruction at the primary level.